From Bureaucratic-Centralism Management to School Based Management: Managing Human Resources in the Management of Education Program - Asad, Asad (Indonesian Research Journal in Education |IRJE|, 2021)
Indonesiaâ€™s education system used to be a centralized and bureaucratic mode as introduced by the Dutch as the colonial power. However, after the fall of Suhartoâ€™s administration in May 1998, the Indonesian education policy has significantly transformed from centralization to decentralization - which is popularly known as school-based management (SBM). This change is because of the arrival of the Law No.22/1999 (later reviewed by the Law 32/2004) about â€œLocal Governmentâ€ (provinces and districts). The purposes of this paper are first to discuss the characteristics of school-based management and the practices of SBM and second, to explore the motives of Indonesian government to apply school-based management in education in the digital era. The orienting question for this study is: Are all school-levels actors and district level actors ready for dealing with the characteristics of school-based management and the practices of SBM? Recommendations for education policy reform in the digital era in Indonesia for good governance are discussed, particularly the motives to move from bureaucratic-centralism management to school-based management.